(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
We study the generation of atomic-squeezed states for a Bose-Einstein Condensate confined within the lossless optomechanical cavity using pondermotively squeezed light. We show that the radiation pressure coupling between the optical cavity field and mechanical motion of the cavity end mirror generates squeezing of light. This radiation pressure induced light squeezing gets transferred to the condensate atoms via Tavis-Cummings type interaction and results in squeezed-spin states. We further discuss the effect of optomechanical coupling on squeezed atomic states.